SNOW TEMPERATURE MEASUREMENTS AT VOSTOK STATION FROM AN AUTONOMOUS RECORDING SYSTEM (TAUTO): PRELIMINARY RESULTS FROM THE FIRST YEAR OPERATION - E. Lefebvre; L. Arnaud; A. A. Ekaykin; V. Y. Lipenkov; G. Picard; J.-R. Petit (Лëд и снег, 2015)
Temperature gradients in the upper layers of the snow pack are of importance for studying the emissivity properties of the snow surface with respect to microwaves used in remote sensing as well as for the heat and mass transfer in snow thickness. Gradients drive the initial snow microstructure metamorphisms that probably influence the firn properties in regard to air molecules fractionation and the air bubble enclosure process at close-off depths. As a contribution to investigation of these problems and following J.-M. Barnola initiative, we developed an autonomous recording system to monitor the temperature of the upper layers of the snow pack. The instrument was built to be autonomous and to be continuously operating within environmental conditions of the Antarctic plateau and the polar night. The apparatus which monitors temperature from the first 10 mof snow by 15 sensors of a «temperature grape» was set at Vostok station during 55th Russian Antarctic Expedition within the frame of the French Russian collaboration (GDRI Vostok). From the available hourly measurements over the first year, we present preliminary results on the thermal diffusive properties of the snow pack as well as some character of the temperature variations on the Antarctic plateau.